2016
DOI: 10.1080/10426914.2016.1198029
|View full text |Cite
|
Sign up to set email alerts
|

Feed-direction ultrasonic vibration−assisted milling surface texture formation

Abstract: The formation mechanism of surface texture for feed-direction ultrasonic vibration assisted milling was investigated in this study by establishing a kinematic model and a pressing model of ultrasonic vibration assisted milling (UVAM). The kinematic model showed that the cutter tip which was supposed to be totally sharp produced closed scratches by crossed trajectories. The variation trends of the interval for closed textures were of sin function. A comparative experiment was carried out by UVAM and conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Figure 6 can clear illustrate the difference about cutting force both in the UVAM and CM process. In the UVAM process, the cutting force in 20 s is much lower than that by CM process both in the maximum force value and the average force value [18]. Ultrasonic vibration cutting force is uniform in a short period occupying whole cutting data time, at the same time, the cutting force in CM process is changing slowly and much higher than the ultrasonic one.…”
Section: Cutting Force and Chips Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…Figure 6 can clear illustrate the difference about cutting force both in the UVAM and CM process. In the UVAM process, the cutting force in 20 s is much lower than that by CM process both in the maximum force value and the average force value [18]. Ultrasonic vibration cutting force is uniform in a short period occupying whole cutting data time, at the same time, the cutting force in CM process is changing slowly and much higher than the ultrasonic one.…”
Section: Cutting Force and Chips Analysismentioning
confidence: 92%
“…Tao et al proposed a kinematic model and a pressing model for the formation mechanism of surface texture for feed-direction ultrasonic vibration assisted milling . But this research had less pay attention on the overlapping machining area [18]. Applying ultrasonic vibration in the feed direction [19][20] and main shaft axial direction [21] could change the surface quality via matching different cutting parameters.…”
Section: Introductionmentioning
confidence: 99%
“…18 Cross-cut metallography slides for: a conventionally and b 20 kHz ultrasonically machined coupons Fig. 19 Carp surface and SEM photo of the VAMilling surface [95] length) and consequently reducing tool contact length, is recognized as one of the main reasons to reduce the cutting force [87]. During the elliptical motion of tool tip in VAM, the average force is reduced and this reduced tool cutting force has also been shown to reduce chatter [88] on the surface produced.…”
Section: Tool Life Extensionmentioning
confidence: 99%
“…There is an emerging trend to obtain biomimetic surface texture and certain surface performance through VAM. Tao et al [95] produced the squamous surface by VAMilling as shown in Fig. 19.…”
Section: Tool Life Extensionmentioning
confidence: 99%
“…In this model, although the tool profile was mapped along tool path to consider the effects of multiple tool engagements on surface generation, the effects of the tool geometry was still overlooked. Tao et al (2017) also analyzed the influence of tool parameters on surface generation, they simplified the tool cutting edge as a sharp one, to simple the simulation process and reduce the computation time, but it reduces the accuracy of the surface texture simulation. Recently, Börner et al (2018) proposed an improved modelling model for textured surface generation in VAMILL.…”
Section: Introductionmentioning
confidence: 99%